Development Strategy of Beef Cattle Business to Increase Farmers' Economic Value in Sukabumi Regency - S Rusdiana; Andi B. Lompengeng Ishak; Teuku Reza Ferasyi (The Faculty of Veterinary Medicine of Syiah Kuala University, 2020)
The research objective was to determine the beef cattle business development strategy in increasing the economic value of farmers in Sukabumi Regency. The research was conducted in Ciracap District, Sukabumi Regency, West Java in 2020. The research used survey methods and interviews with 65 farmers and 9 extension workers from BPP Sukabumi Regency. Primary data and secondary data were analyzed using statistical analysis, economic analysis and Swot analysis descriptively and quantitatively. The results showed that the farmers' average land ownership was 1.57 ha/farmer. The farmer profit is IDR. 250.548.975 /year, the value of R/C is 1.14. The related variable (dependent) which affects farmer profit and business efficiency of beef cattle has an effect on the95% confidence level. Swot analysis of internal and external factors in the development of beef cattle business showed the strengths of the working area of the Sukabumi Regency BPP including available labor, agricultural land area, grazing land, the number of cows being raised and the support of government institutions, private companies and other institutions as well as livestock market opportunities wide open. The weaknesses are limited land resources, business capital, increased feed prices and the price of beef cattle that were controlled by middlemen. It is suggested that strategies to increase beef cattle population and economic value of the farmers are by optimizing the function of empty land as grazing land and forage cultivation. Business cooperation, marketing networks and guaranteed beef cattle prices are pivotal in order to take advantage of relatively unfulfilled market opportunities.